The Effect of Entrepreneurial Literacy on Financial Inclusion and Capital Market Investment Understanding through the Development of MSMEs - Thamrin Tahir; Muhammad Ilyas Thamrin Tahir; Sumiati Tahir; Sheerad Sahid (International Journal of Economics, Business and Innovation Research, 2024)
This research is an effort to see the influence of entrepreneurial literacy on financial inclusion and investment understanding through the development of MSMEs in Makassar. The study aims to see: 1) there is an influence of entrepreneurial literacy on the financial inclusion of MSMEs in Makassar City. 2) there is an influence of entrepreneurial literacy on the understanding of MSME investment in Makassar City. 3) there is an influence of entrepreneurial literacy on the development of MSMEs in Makassar City. 4) there is an influence of MSME development on financial inclusion and understanding of MSME investment in Makassar City. And 5) there is an influence of entrepreneurial literacy on financial inclusion and investment understanding through the development of MSMEs in Makassar City. This research is an explanatory research and the design of this study uses a quantitative approach. And this research was processed using SEM and several software (software) for data processing processes such as, Microsoft Excel 2010, SPSS (Statistical Product and Service Solution) version 20.00. The results obtained are: (1) There is an influence of entrepreneurial literacy on the financial inclusion of MSMEs in Makassar City. (2) There is an influence of entrepreneurial literacy on the understanding of MSME investment in Makassar City. (3) The influence of entrepreneurial literacy on the development of MSMEs in Makassar City is addressed. (4) There is an influence of MSME development on financial inclusion and understanding of MSME investment in Makassar City. And (5) There is an influence of entrepreneurial literacy on financial inclusion and investment understanding through the development of MSMEs in Makassar City.